2021
DOI: 10.26508/lsa.202101108
|View full text |Cite
|
Sign up to set email alerts
|

Microglia show differential transcriptomic response to Aβ peptide aggregates ex vivo and in vivo

Abstract: Aggregation and accumulation of amyloid-β (Aβ) is a defining feature of Alzheimer’s disease pathology. To study microglial responses to Aβ, we applied exogenous Aβ peptide, in either oligomeric or fibrillar conformation, to primary mouse microglial cultures and evaluated system-level transcriptional changes and then compared these with transcriptomic changes in the brains of CRND8 APP mice. We find that primary microglial cultures have rapid and massive transcriptional change in response to Aβ. Transcriptomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 75 publications
3
18
0
Order By: Relevance
“…Microglia in vitro and in the brain also have different responses to Aβ. Murine primary microglia display rapid and substantial transcriptional changes in response to Aβ, while in vivo microglia do not display the same gene expression changes, suggesting that primary microglia poorly recapitulate in vivo conditions ( McFarland et al, 2021 ). Nevertheless, studies have shown that culturing microglia together with neurons can mitigate this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia in vitro and in the brain also have different responses to Aβ. Murine primary microglia display rapid and substantial transcriptional changes in response to Aβ, while in vivo microglia do not display the same gene expression changes, suggesting that primary microglia poorly recapitulate in vivo conditions ( McFarland et al, 2021 ). Nevertheless, studies have shown that culturing microglia together with neurons can mitigate this problem.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cellular and anatomical complexity of in vivo models may limit further mechanistic insight and cell type-specific intervention in the communication between neurons, astrocytes and microglia. On the other hand, 2D in vitro monocultures lack the in vivo complexity to accurately model the physiological and pathological responses of neural cells in general, and microglia in particular [ 67 , 69 ] similar to astrocytes, as mentioned above. For ß-amyloid formation, a 3D neuron/astrocyte/microglia tri-culture has been developed using immortalized microglia [ 28 ], but no 3D tri-culture of tau aggregation exists yet.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the association ( p -value) was reported following Tukey’s correction. To calculate the cell-type-specific DEGs and neurodegeneration-associated glial gene expression signatures, the geometric means of a set of genes characterizing each profile were used, as described before [ 69 ]. Briefly, we used a transcriptomic database which compiled the expression from RNA sequencing from different cell types (neurons, astrocytes, microglia, newly formed oligodendrocytes, endothelial cells and pericytes) in the brain [ 70 ] to generate lists of genes whose expression was enriched in each representative cell type ( Table S2 ).…”
Section: Methodsmentioning
confidence: 99%